2003
DOI: 10.1161/01.cir.0000080895.05158.8b
|View full text |Cite
|
Sign up to set email alerts
|

Statins Promote Potent Systemic Antioxidant Effects Through Specific Inflammatory Pathways

Abstract: Background-The pleiotropic actions of hydroxymethylglutaryl CoA reductase inhibitors (statins) include antiinflammatory and antioxidant actions. We recently reported that statins induce reductions in plasma protein levels of nitrotyrosine (NO 2 Tyr), a modification generated by nitric oxide-derived oxidants. Whether alternative oxidative pathways are suppressed in vivo after statin administration has not yet been reported. Methods and Results-As an extension of our prior study, hypercholesterolemic subjects wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
239
2
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 368 publications
(255 citation statements)
references
References 44 publications
7
239
2
7
Order By: Relevance
“…The mechanisms behind the antiarrhythmic effect of statins remain unclear but are possibly attributable to improvement in inflammation, oxidative stress, and endothelial dysfunction 32, 33, 34. Nonimprovement in endothelial function by atorvastatin treatment in this study likely affected the lack of benefit for arrhythmia recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms behind the antiarrhythmic effect of statins remain unclear but are possibly attributable to improvement in inflammation, oxidative stress, and endothelial dysfunction 32, 33, 34. Nonimprovement in endothelial function by atorvastatin treatment in this study likely affected the lack of benefit for arrhythmia recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, elevated plasma MPO levels predict the risk of cardiovascular events and mortality in patients with unstable angina, chest pain (37), acute coronary syndrome, or peripheral arterial disease (37)(38)(39)(40). Systemic levels of 3-nitrotyrosine have also been found to be higher among patients with CVD compared to those with healthy arteries (41)(42)(43). We have recently demonstrated that plasma MPO levels and MPO oxidation products are elevated in autoimmune diseases such as rheumatoid arthritis and systemic lupus erythematous, both of which carry an increased risk of CVD (44,45).…”
Section: Myeloperoxidase Oxidizes Artery Proteins In Kidney Diseasementioning
confidence: 99%
“…Systemic or intraperitoneal injection of CYP induces a reproducible dose-dependant chemical cystitis in both mice and rats and therefore has been used as an experimental model of cystitis 11 . Although statins are not employed in the treatment of HC, we hypothesized that their use may be useful due to their pleiotropic anti-inflammatory effects 12 . We did not find reports in the literature on the use of statins in clinical and experimental studies involving HC induced by CYP.…”
Section: Introductionmentioning
confidence: 99%